2004
DOI: 10.2108/zsj.21.691
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Control of Meiosis Initiation in the Testis from Japanese Newt, Cynops pyrrhogaster

Abstract: Meiosis is an event that occurs prerequisitely and specifically in gametogenesis. However, the mechanisms of conversion from mitosis to meiosis are poorly understood. I will review the results so far obtained by us using newt testis as a model system, and discuss about the extrinsic mechanism(s) controlling the conversion from mitosis to meiosis. In the newt spermatogonia enter meiosis in the 8th generation after 7 mitotic divisions. We developed organ and reaggregate culture systems with a chemically defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…In the testis of the Japanese red-bellied newt, Cynops pyrrhogaster, primary spermatogonia proliferate through seven mitotic divisions, and then in the 8th generation the spermatogonia differentiate into primary spermatocytes and initiate meiosis in the spring when the ambient temperature is high; in contrast, in the autumn when the ambient temperature is low, the spermatogonia often undergo apoptosis in the 7th generation, resulting in the cessation of spermatogenesis (2). These findings suggest the existence of molecular mechanisms regulating the fate of 7th generation spermatogonia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the testis of the Japanese red-bellied newt, Cynops pyrrhogaster, primary spermatogonia proliferate through seven mitotic divisions, and then in the 8th generation the spermatogonia differentiate into primary spermatocytes and initiate meiosis in the spring when the ambient temperature is high; in contrast, in the autumn when the ambient temperature is low, the spermatogonia often undergo apoptosis in the 7th generation, resulting in the cessation of spermatogenesis (2). These findings suggest the existence of molecular mechanisms regulating the fate of 7th generation spermatogonia.…”
mentioning
confidence: 99%
“…The germ cells are in close contact with somatic Sertoli cells in a spermatogenic cyst, the smallest unit of the testis. The testis consists of lobules in successive zones arranged along a cephalocaudal axis, in which spermatogenesis proceeds synchronously (2,6). Therefore, we can dissect zones containing particular spermatogenic stages and identify the generation of spermatogonia by counting their numbers in a cyst.…”
mentioning
confidence: 99%
“…Effect of nNRG1 antibody on the spermatogonial proliferation induced by nNRG1 and FSH FSH induces newt spermatogonial proliferation and their differentiation through its receptor expressed on Sertoli cells (Abé , 2004). In order to examine whether FSH promotes spermatogonial proliferation by activating Sertoli cells to produce nNRG1, antibody against EGF-like domain of nNRG1 (antinNRG1-EGF) was added to the reaggregated culture of testicular cells.…”
Section: 5mentioning
confidence: 99%
“…In newt testis, we have demonstrated that FSH alone is sufficient to stimulate spermatogonial proliferation and differentiation into primary spermatocytes through the receptor expressed on Sertoli cells in both organ and reaggregate cultures (Abé and Ji, 1994;Abé , 2004), but not in the culture of spermatogonia alone (Ito and Abé , 1999). In addition, we reported that SCF and IGF-I, both of which are upregulated in response to FSH (unpublished data; Yamamoto et al, 2001), induce spermatogonial proliferation (Abé et al, 2002) and differentiation (Nakayama et al, 1999), respectively, in the organ culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation